2012
DOI: 10.1038/srep01002
|View full text |Cite
|
Sign up to set email alerts
|

PINK1-mediated phosphorylation of the Parkin ubiquitin-like domain primes mitochondrial translocation of Parkin and regulates mitophagy

Abstract: Parkinson's disease genes PINK1 and parkin encode kinase and ubiquitin ligase, respectively. The gene products PINK1 and Parkin are implicated in mitochondrial autophagy, or mitophagy. Upon the loss of mitochondrial membrane potential (ΔΨm), cytosolic Parkin is recruited to the mitochondria by PINK1 through an uncharacterised mechanism – an initial step triggering sequential events in mitophagy. This study reports that Ser65 in the ubiquitin-like domain (Ubl) of Parkin is phosphorylated in a PINK1-dependent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
424
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 504 publications
(455 citation statements)
references
References 46 publications
(83 reference statements)
18
424
1
2
Order By: Relevance
“…In line with this observation, Pink1 has been shown to interact with Parkin [22]. Furthermore, recent studies showed that Pink1 can autophosphorylate itself and directly or indirectly trigger Parkin phosphorylation, which may activate its E3 ligase activity [23][24][25]. Parkin belongs to the RBR (RING-in-Between-RING) E3 ligase family, which has two tandem RING domains.…”
Section: Introductionmentioning
confidence: 76%
“…In line with this observation, Pink1 has been shown to interact with Parkin [22]. Furthermore, recent studies showed that Pink1 can autophosphorylate itself and directly or indirectly trigger Parkin phosphorylation, which may activate its E3 ligase activity [23][24][25]. Parkin belongs to the RBR (RING-in-Between-RING) E3 ligase family, which has two tandem RING domains.…”
Section: Introductionmentioning
confidence: 76%
“…Rather, this step optimizes parkin for Ubl phosphorylation and E2~Ub engagement (Fig 6B; Kumar et al , 2015; Ordureau et al , 2015). It is well established that phosphorylation of the Ubl domain following pUb recruitment significantly increases its ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014). Current NMR dynamics analysis of R0RBR parkin:pUb as a proxy for this state shows the IBR domain is considerably less mobile due to engagement with pUb although a large stretch of the tether region remains mobile, an observation not obvious from current crystal structures.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn helps recruit parkin to the membrane through binding of pUb to the RING1–IBR region of the E3 ligase (Sauvé et al , 2015; Wauer et al , 2015; Kumar et al , 2017) and subsequent phosphorylation of parkin's Ubl (pUbl) domain (Ordureau et al , 2014). These two events greatly stimulate ubiquitination activity (Kondapalli et al , 2012; Shiba‐Fukushima et al , 2012; Kane et al , 2014; Kazlauskaite et al , 2014; Koyano et al , 2014) through an allosteric displacement mechanism of the pUbl domain from parkin (Kumar et al , 2015; Sauvé et al , 2015). What is less clear is how parkin positions the E2~Ub conjugate to enable transfer of the Ub molecule to the RING2(Rcat) domain as a necessary step for catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Threedimensional structures of parkin show UBL associates with the C-terminal region (R0RBR) through both ionic and hydrophobic interactions, blocking the proposed E2 recognition site (14,15). PINK1 stimulates parkin activity through phosphorylation of both Ub and parkin's UBL domain at an equivalent serine 65 position in sequence and structure (16)(17)(18)(19)(20)(21). Whereas each phosphorylation event can increase parkin activity independently, maximal activity is obtained when both parkin and Ub are phosphorylated (18,19).…”
mentioning
confidence: 99%